Research on Application and Optimization of Intelligent Diagnosis Technology in Power Line Loss Management - Wu, Jianbo; Xia, Zeju; Li, Rui; Liu, Rundong (Distributed Generation & Alternative Energy Journal, 2026)
Power line loss management faces challenges such as massive data processing, real-time diagnosis accuracy, data security guarantee and system adaptive optimisation. It is urgent to improve diagnosis efficiency and management effect by applying and optimising intelligent diagnosis technology. This paper systematically studies the application and optimization of intelligent diagnosis technology in power line loss management. It constructs a multi-level diagnosis system integrating multiple technologies, where distributed streaming computing enables real-time processing of massive time-series data from smart meters and SCADA systems; trusted computing mechanism ensures data security through hardware-level authentication; spatiotemporal graph neural network models the spatiotemporal correlation of power grid nodes; federated learning realizes collaborative model optimization without data sharing; multi-objective evolutionary optimization improves parameter tuning efficiency; and digital twin achieves dynamic mapping of physical grid operations for continuous learning. According to the data of 200 monitoring points in this area, through the analysis of the intelligent diagnosis system, it is found that 23.5% of monitoring points have abnormal line loss fluctuations in varying degrees, 78.2% of the fluctuations are due to poor contact caused by equipment ageing, and normal equipment loss accounts for only 45%. After accurate positioning using intelligent diagnosis technology and targeted repair, the power line loss rate in this area decreased by 67.89%. In comparison, the meter reading accuracy increased from 32.1% to 90.5%, and the processing efficiency of abnormal work orders increased by 12.34 times, effectively reducing manual operation and maintenance costs, saving about 56.7% of operation and maintenance time, and providing strong data support and technical support for power line loss management.